Compensation of self-heating-induced timing errors in bipolar comparators. (January 2016) - Webb, Kyle M.; Kalkur, T.S.
Abstract: Self-heating effects in bipolar comparators manifest themselves as signal-dependent output signal timing variation. In applications where comparator circuits are used for precise timing measurement of input signal threshold crossings, such as test and measurement instruments, self-heating presents a design challenge that must be addressed. A comparator circuit, utilizing a novel circuit-based self-heating compensation method, has been designed and fabricated in a BiCMOS HBT process. This self-heating compensation scheme differs from previously reported compensation circuitry in that it is designed for the compensation of asynchronous comparators. Measurements presented here demonstrate the effectiveness of the compensation circuitry at reducing self-heating-induced timing errors over a wide range of input signal amplitude and common-mode voltage.